Corrected by Reflection: The De-anthropomorphized Mindset of Atheism. (23rd January 2017) - Talbot, Elizabeth; Wastell, Colin
Abstract : Cognitive by-product theorists suggest that the ability to accept religious and supernatural belief is a by-product of humans' evolved propensity to over-attribute agency to non-human entities such as animals and objects. It is argued that this phenomenon facilitates and underpins belief in gods and supernatural beings. With this in mind, how then is non belief and atheism explained? The present study aimed to explore atheism from the perspective of by-product theory, examining differences in Anthropomorphizing (attributing human qualities to non human entities) in a population of atheists compared to a sample from a general population. One hundred and twenty-three participants recruited from a general population for a study on beliefs and thirty-six participants were recruited via an atheist organization completed the study. Results showed lower use of non-animal agency anthropomorphic concepts was linked to lower religiosity, and that the atheist recruited participants showed the least endorsement of anthropomorphic concepts than the general population sample. The implications of this finding are discussed with respect to the nature of atheism and the role of de-anthropomorphizing in the adoption of an atheist belief position.